ENGINE PERFORMANCE ANALYSIS OF PALM KERNEL OIL-BASED BIODIESEL BLENDS ON SPEED VARIATIONS OF A 4-CYLINDER ENGINE AT CONSTANT TORQUE - Chukwudi Okwuchukwu, Aniagor (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2023)
Biodiesel made from the transesterification of plant-derived oils is an important alternative fuel source for diesel engines. Several disparate studies have emphasized the significance of biodiesels in emission reduction and engine efficiency. The present study examined the effect of using palm kernel oil (PKO), pure petroleum diesel, and its blends on the fuel consumption rates, energy expended, brake-specific fuel consumption, and brake thermal efficiency of a four-cylinder tractor under varying operating speeds (700 – 1900rpm) at constant torque. The study was conducted at a large farming site in Anambra State, Nigeria. The findings indicated that PKO biodiesel blends had the overall optimum energy output, fuel consumption rates, and brake-specific fuel consumption, respectively, at the highest engine speed of 1900. Although B10's rating of 60.6% for thermal brake efficiency was impressive, it was lower than B100's 66.95 %. Based on the results, B10 is the best gasoline for testing and may be used as a replacement fuel in four-cylinder farm tractor engines with no modifications. The study concludes that biodiesel blends showed potential as an alternative to fossil diesel.